The Prospects and challenges of women priesthood in the Anglican church Harare diocese - Mutukwa, W. (BUSE, 2020)
The study sought to investigate the prospects and challenges of women priesthood in the Anglican Church Harare Diocese. Theoretical framework: The Feminist Peace and Conflict Theory (FPCT); the Conflict transformation of Lederach, John Paul and the Marxist Feminist theory guided the study. Method: A mixed research paradigm and a case study design were employed. The population of the study was 400 prospective respondents and was comprised of reverends, priests, elders, deacons and deaconess. Purposive and random sampling techniques were used to come up with the study sample of 45 people comprised of 5 Reverends; 10 priests; 10 elders, 10 deacons and 10 deaconess. Questionnaires, in-depth interviews and observations were used to collected data in the study. Findings: Congregational conflicts over beliefs and values the need to change from traditional way of doing things, equality issue and the down of democracy is contributing to the demand for women priesthood in the Anglican Church. The ordination of women symbolically distorts the scriptural revelation of God. Opportunities: Ordaining women promotes democracy reducing violence and increase justice in the Anglican Church Harare Diocese. Challenges: women experience sexual harassment, abuse and isolation if ordained as priests. Recommendations: promote women priesthood and change to church beliefs over women priesthood in the Anglican Church. There is need to address the gender inequality gap in the Anglican Church Harare Diocese